Drinking and driving: characteristics of drivers with positive breathalyzer - Campos, Valdir Ribeiro (2012)
CONTEXT: Drinking and driving has not been adequately studied in Brazil so far. OBJECTIVE: The present study presents data from the first survey on drinking and driving behavior in a Brazilian state. METHOD: One thousand seven hundred ninety-nine anonymous interviews were conducted with drivers at sobriety checkpoints in ten cities representing the ten geographic regions of the state of Minas Gerais. Of those drivers, 1,209 (67.2%) responded to a subsequent structured questionnaire and agreed to take a breathalyzer test. RESULTS: Twenty percent of the drivers were driving with blood alcohol levels over the legal limit. Logistic regression analysis, controlled by sex, was used to predict positive breathalyzer test. Drivers over the age of 31 years with an alcohol consumption frequency of at least 1-2 days per week, who were not using seat belts, showed an increased probability of positive breathalyzer test. DISCUSSION: Studies with a similar methodology conducted in sobriety checkpoints can monitor the behavior of drivers and risks in traffic, and direct public policy on drinking and driving.